Hi I am trying to prove this $$ I:=\int_{0}^{1} {x\log\left(\,x\,\right) + 1 - x \over x\log^{2}\left(\,x\,\right)}\, \log\left(\,1 + x\,\right)\,{\rm d}x=\log\left(\,4 \over \pi\,\right). $$ Thanks.

This is just a beautiful integral for many reasons. Logs are everywhere and an inspirational solution!!! I am not sure if breaking it up into three separate pieces is of any use, I tried that by writing $$ I=\int_0^1\frac{ \log(1+x)}{\log x}dx+\int_0^1\frac{\log(1+x)}{x \log^2 x}dx-\int_0^1\frac{\log(1+x)}{\log^2 x}dx $$ but wasn't sure how to handle these. Also note that $$ \int_0^1 \frac{x\log x+1-x}{x \log^2 x}dx=1, $$ in case that happened to come up anywhere along the calculation.

  • $\begingroup$ Can you share where you are getting these? I know you say you used to compete in math competitions - can we see any of those resources? $\endgroup$ – Bennett Gardiner May 8 '14 at 4:34
  • $\begingroup$ @BennettGardiner This is from Ryzhik's book on integrals (russian version). Others I post are from Demidovich - Problems in mathematical analysis (russian copy). A lot are also from Borwein papers. Many integrals I post are not from books and are just from my notes, so those resources were the city teachers & from competitions. The rest are from being an integral fanatic for 40 years. $\endgroup$ – Jeff Faraci May 8 '14 at 4:54
  • $\begingroup$ @BennettGardiner Does this help? Thanks. $\endgroup$ – Jeff Faraci May 8 '14 at 4:55
  • $\begingroup$ Jeff, please send me all of your integral resources. This is my email: ariawan.11@gmail.com. Thank you. :) $\endgroup$ – Tunk-Fey May 8 '14 at 5:03
  • 2
    $\begingroup$ The three separate pieces you wrote down all diverge, so I'm pretty sure that this is not the way to go. Beautiful integral, though. $\endgroup$ – user111187 May 8 '14 at 6:46

Consider \begin{align*} \int_0^1 \frac{x\log{x}+1-x}{x}\, x^a\, \log{(1+x)}\, dx &= \int_0^1 \frac{x\log{x}+1-x}{x}\, x^a\, \sum_{n\ge 1} (-1)^{n+1}\frac{x^n}{n}\, dx\\ &=\sum_{n\ge 1} \int_0^1 \, (-1)^{n+1} (x\log{x}+1-x)\, \frac{x^{a+n-1}}{n}\, dx\\ &= \sum_{n\ge 1} - \frac{\left(-1\right)^{n+1}}{{\left(a + n + 1\right)}^{2} n} + \frac{\left(-1\right)^{n+1}}{{\left(a + n\right)} n} -\frac{\left(-1\right)^{n+1}}{{\left(a + n + 1\right)} n}\\ \int_0^1 \frac{x\log{x}+1-x}{x \log{x}}\, x^a\, \log{(1+x)}\, dx &= \sum_{n\ge 1} \frac{\left(-1\right)^{n + 1}}{n} \left(\frac{1}{a + n + 1} + \log\left(\frac{a + n}{a+n+1}\right)\right)\tag{$\int da$}\\ \int_0^1 \frac{x\log{x}+1-x}{x (\log{x})^2}\, x^a\, \log{(1+x)}\, dx &= \sum_{n\ge 1} \frac{\left(-1\right)^{n+1} {\left(a + n\right)} \log\left(\frac{a + n}{a + n + 1}\right) + \left(-1\right)^{n+1}}{n}\tag{$\int da$}\\ \end{align*} Subst. $a=0$ \begin{align*} \therefore \int_0^1 \frac{x\log{x}+1-x}{x (\log{x})^2}\, \log{(1+x)}\, dx &= \sum_{n\ge 1} \left(-1\right)^{n+1} \log\left(\frac{ n}{ n + 1}\right) + \frac{\left(-1\right)^{n+1}}{n}\hspace{20pt} \text{(Wallis product and log 2)}\\ &= \log{\left(\frac{2}{\pi}\right)}+\log{2} \\ &= \log{\left(\frac{4}{\pi}\right)} \end{align*}

  • $\begingroup$ Nice, you found a more direct method. $\endgroup$ – user111187 May 9 '14 at 16:59
  • $\begingroup$ Thanks.. I was hoping to get a general formula here also, but the summation looks difficult. $\endgroup$ – gar May 9 '14 at 17:33

Substituting $\log x = -u$ gives $$ I = \int_0^{\infty} \frac{1-(x+1)e^{-x}}{x^2} \ln(1+e^{-x}) $$ Noticing that $\frac{d}{dx} (e^{-x}-1)/x = \frac{1-(x+1)e^{-x}}{x^2}$, we integrate by parts to obtain $$ I = -\ln 2- \int_0^{\infty} \frac{dx}{x}e^{-x} \frac{1-e^{-x}}{1+e^{-x}} $$ So the problem is reduced to showing that $$J:=\int_0^{\infty} \frac{dx}{x}e^{-x} \frac{1-e^{-x}}{1+e^{-x}}=\ln{\frac{\pi}{2}}$$ We have $$J = \sum_{k\geq0} (-1)^{k} \int_0^{\infty} \frac{dx}{x} \left( e^{-x}-e^{-2x}\right)e^{-kx} $$ (Here I used the geometric series and interchanged summation and integration.) $$ = \sum_{k\geq0} (-1)^{k} \ln \frac{k+2}{k+1} $$ $$ = \sum_{k\geq1} (-1)^{k-1} \ln \left( 1+\frac{1}{k} \right) $$ (Here I used a well-known integral that follows from Frullani's theorem)

$$ = \sum_{k\geq1} \left[ \ln\left( 1+\frac{1}{2k-1}\right)-\ln\left( 1+\frac{1}{2k}\right) \right] \\ = \lim_{N\rightarrow\infty} \ln\left[ \prod_{k=0}^N \frac{1+\frac{1}{2k-1}}{1+\frac{1}{2k}} \right] \\ = \ln \left[ \lim_{N\rightarrow\infty} \prod_{k=0}^N \frac{4k^2}{4k^2-1} \right] \\ = -\ln \left[\prod_{k\geq0} \left( 1-\frac{1}{4k^2} \right) \right]\\ = -\ln \left[ \frac{\sin(\pi /2)} {\pi/2} \right]$$ Here I used the product formula for $\frac{\sin \pi x}{\pi x}$ Hence $$ J= \ln \frac{\pi}{2} $$ as was to be proved.

  • $\begingroup$ Very nice answer. +1 $\endgroup$ – Random Variable May 8 '14 at 16:26
  • $\begingroup$ @RandomVariable Thank you, a big compliment coming from you! $\endgroup$ – user111187 May 8 '14 at 16:33
  • $\begingroup$ This is very nice indeed! +1 $\endgroup$ – Pranav Arora May 8 '14 at 16:47
  • $\begingroup$ @user111187: Can you please share a link about the product formula you used in the end? I managed to reach the final product (though my method isn't as elegant as yours) but didn't know how to evaluate the product. Thanks! $\endgroup$ – Pranav Arora May 8 '14 at 16:49
  • 1
    $\begingroup$ @PranavArora A derivation of the formula that does not require complex analysis or advanced methods is given here: ocw.mit.edu/courses/mathematics/… $\endgroup$ – user111187 May 8 '14 at 16:53

Note $$\frac{1}{x\log^2x}=-\frac{d}{dx}\frac{1}{\log x} $$ and hence \begin{eqnarray} I&=&\int_{0}^{1} {x\log\left(\,x\,\right) + 1 - x \over x\log^{2}\left(\,x\,\right)}\, \log\left(\,1 + x\,\right)\,{\rm d}x\\ &=&-\int_{0}^{1} (x\log x + 1 - x)\log(1+x)d\frac{1}{\log x}\\ &=&-(x\log x + 1 - x)\log(1+x)\frac{1}{\log x}\bigg|_0^1+\int_{0}^{1}\frac{1}{\log x}d[ (x\log x + 1 - x)\log(1+x)]\\ &=&\int_0^1\frac{1}{\log x}\left(\frac{x \log x+1-x}{x+1}+\log x \log (x+1)\right)dx\\ &=&\int_0^1\log(x+1)dx+\int_0^1\frac{x}{x+1}+\int_0^1\frac{1}{\log x}\frac{1-x}{x+1}dx\\ &=&\log 2+J, \end{eqnarray} where $$ J=\int_0^1\frac{1}{\log x}\frac{1-x}{x+1}dx.$$ Define $$ f(a)=\int_0^1x^a\frac{1-x}{x+1}dx. $$ Then \begin{eqnarray} f(a)&=&\int_0^1\sum_{n=0}^\infty(-1)^nx^{a+n}(1-x)dx &=&\sum_{n=0}^\infty(-1)^n\left(\frac{1}{n+a+1}-\frac{1}{n+a+2}\right) \end{eqnarray} and hence $$ \int_0^a f(a)da=\sum_{n=0}^\infty(-1)^n\log\frac{n+a+1}{n+a+2},$$ and $$ J=\lim_{a\to0}\sum_{n=0}^\infty(-1)^n\log\frac{n+a+1}{n+a+2}=\sum_{n=0}^\infty(-1)^n\log\frac{n+1}{n+2}=\log\frac{2}{\pi}.$$ Thus $$ I=\log\frac{4}{\pi}. $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.